2005
DOI: 10.1039/b417071g
|View full text |Cite
|
Sign up to set email alerts
|

Counter-ions dynamics in highly plastic and conducting compounds of poly(aniline). A quasi-elastic neutron scattering study

Abstract: Proton dynamics in films of poly(aniline) "plastdoped" with di-esters of sulfophthalic (or sulfosuccinic) acids have been investigated by using quasi-elastic neutron scattering techniques. A broad time range (10(-13)-10(-9) s) has been explored by using four different spectrometers. In this time range, the dynamics is exclusively due to protons attached to the flexible tails of the counter-ions. A model of limited diffusion in spheres whose radii are distributed in size gives a realistic view of the geometry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…44 Similar values were determined by Doxastakis et al 58 using QENS and molecular simulations on freeze-dried head-deuterated DPPC LUVs in their liquid phase. In contrast, Djurado et al 62 determined several hydrogen atom populations in lipid lms that perform diffusion in spheres of different radii.…”
Section: Dynamical Properties Of the Membranesmentioning
confidence: 99%
“…44 Similar values were determined by Doxastakis et al 58 using QENS and molecular simulations on freeze-dried head-deuterated DPPC LUVs in their liquid phase. In contrast, Djurado et al 62 determined several hydrogen atom populations in lipid lms that perform diffusion in spheres of different radii.…”
Section: Dynamical Properties Of the Membranesmentioning
confidence: 99%
“…The Time Distribution of Molecular Dynamics in ''Plastdoped'' PANI [9] One of the most surprising features we found for the dynamics of these systems is the very broad distribution of their characteristic times. Indeed, several spectrometers with different energy resolutions were used in order to span the broadest time range possible (10 À13 to 10 À9 s) and whatever the resolution of the spectrometer, we found the same values for the elastic incoherent structure factors (EISF) [9] (see Figure 4). This result means the observed motion of protons has a broad range of time characteristics.…”
Section: Figurementioning
confidence: 82%
“…The Geometry of Molecular Dynamics in ''Plastdoped'' PANI [7][8][9][10] We studied the molecular dynamics in plastdoped PANI's by using incoherent quasi-elastic neutron scattering techniques [7][8][9] . We showed that most of the dynamics in the 10 À9 -10 À13 s characteristic time range was due to the motion of protons borne by the flexible aliphatic tails of doping counter-ions.…”
Section: Figurementioning
confidence: 99%
“…There are six steps of weight loss occurred during heating cycle under nitrogen atmosphere. The first step of weight loss below may be due to unbound water [19], the second step of weight loss occurring in between may be due to the unbound H 2 SO 4 , the third step of weight loss within may be due to bound water acting as secondary dopant [20]. Differential scanning calorimetric spectrum of untreated and heat treated PANI as shown in Fig.…”
Section: Thermo Gravimetric Analysis (Tga) and Differential Scanning mentioning
confidence: 99%